UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RPP MELALUI WORKSHOP DI SD NEGERI 15 JALAN API KERETA PARIAMAN - Juwita, Ratna (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The research subjects were teachers of SD Negeri 15 Jalan Kereta Api. Research procedure with two cycles. Each cycle consists of two workshops, each of which includes planning, action, observation, and reflection. Data collection techniques with observation, documentation. The data analysis carried out in this study were reduction, data presentation and conclusion drawing. The results revealed that there was an increase in teachers in making learning devices in each cycle. The results of this study indicate that the implementation of the workshops can improve the ability of teachers to compile syllabus and lesson plans as well as increase the number of teachers in preparing these tools. What is expected is achieved.